Turkish EU Membership: A Simulation Study of Economic Effects - Pekka Sulamaa; Mika Widgrén (Aboa Centre for Economics (ACE), 2006)
This paper evaluates the economic effects of Turkish EU membership. The evaluation is based on a widely utilized computable general equilibrium model called GTAP (Global Trade Analysis Project). Imperfect competition is modelled via assumption of scale economies on non agricultural sectors. The latest GTAP database version (base year 2001) is aggregated into seven regions: Turkey, Germany-Austria, North EU, South EU, Balkan countries, NAFTA, ASIA and Rest of World. We analyse economic effects of abolishing trade barriers between the EU25 and Turkey and applying common external tax on Turkey. Major sectoral effects are bound to originate from the agriculture which accounts 11.4 % of Turkey's GDP.
Keywords: C68; F15; F17; 330; GTAP; Turkey; EU enlargement